Antiviral Activity of Extract of Neem (Azadirachta Indica) leaves: An in vivo study - Rukhshan Khurshid, Sadia Majeed, Sumera Saghir, Maheen Saad, Huma Ashraf, Iram Fayyaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: HCV in mainly replicate in liver cell and cause liver damage. The replication of HCV may be inhibited by leaves extract of neem (Azadirachta Indica). Aim: To find the antiviral activity of extract of neem (Azadirachta Indica) leaves. Methods: Thirty five hepatitis C positive and disappointment of conservative treatment were studied. Effect of neem (Azadirachta indica) leaves was seen in serum of patient. Extract of Azadirachta indica leaves was prepared and given orally to patients. The seropositivity of hepatitis C was estimated prior and after the leave extract of neem by HCV- RNA quantitative analysis by Polymerase chain reaction. Level of ALT, AST and total protein were estimated by standard kit methods. Results: A high HCV seropositivity was observed in patients before taking neem extract. We observed that after using the leave extract of Azadirachta indica or neem, the HCV seropositivity was significantly decreased. Levels of enzymes ALT and AST were also significantly decreased after taking neem extract. However, the level of serum protein was not changed. Conclusion: Extracted leaves of Azadirachta indica may serve as valuable regimen against hepatitis C virus as it has an ability to inhibit the protease responsible for replication of virus.